Prospects and Challenges of ELT at a Glance - Khadka, Kabita (Journal of Janta Multiple Campus, 2024)
English has been utilized for more than 150 years as the primary language of instruction, evaluation system, and subject matter to be taught and learned, or both, covering a broad variety of subjects from early childhood to higher education (Khadka, 2022). This paper uses the qualitative method, relying on secondary sources of data. An overview of teaching English in Nepal is provided in this article. It makes an effort to investigate how teaching and learning languages are situational. The study aims to discuss Nepal's ELT paradigm shift along with societal inequality and disparity, which lead to difficulties in English language instruction in Nepal. How an English language education practitioner would address those challenges is covered in the paper's conclusion.